2007
DOI: 10.1016/j.schres.2007.07.013
|View full text |Cite
|
Sign up to set email alerts
|

fMRI study of language activation in schizophrenia, schizoaffective disorder and in individuals genetically at high risk

Abstract: Background: Structural and functional abnormalities have been found in language-related brain regions in patients with schizophrenia. We previously reported findings pointing to differences in word processing between people with schizophrenia and individuals who are at high-risk for schizophrenia using a voxel-based (whole brain) fMRI approach. We now extend this finding to specifically examine functional activity in three language related cortical regions using a larger cohort of individuals.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
56
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 94 publications
(61 citation statements)
references
References 35 publications
(43 reference statements)
4
56
0
Order By: Relevance
“…Loss of lateralization in inferior frontal and superior temporal gyri and in parietal lobuli was based on reduced left hemispheric activation in the G-HR subjects, while it was due to increased right side activation in the SCZ group [41]. Compared to the HC, G-HR showed no differences [33] or activated less in language related regions [41], in inferior frontal gyri [35,42], in the cingulate, dorsolateral prefrontal and posterior parietal cortex (especially Val/Val carriers during retrieval [13]).…”
Section: Functional Mri Studies During Verbal Memory In G-hrmentioning
confidence: 91%
See 2 more Smart Citations
“…Loss of lateralization in inferior frontal and superior temporal gyri and in parietal lobuli was based on reduced left hemispheric activation in the G-HR subjects, while it was due to increased right side activation in the SCZ group [41]. Compared to the HC, G-HR showed no differences [33] or activated less in language related regions [41], in inferior frontal gyri [35,42], in the cingulate, dorsolateral prefrontal and posterior parietal cortex (especially Val/Val carriers during retrieval [13]).…”
Section: Functional Mri Studies During Verbal Memory In G-hrmentioning
confidence: 91%
“…All but one [33] of the 13 included studies with G-HR were cross-sectional and mostly examined verbal memory [13, 33-35, 41, 42, 45, 68] and working memory [36,38,43] (Table 2). Five studies based on an overlapping sample from the Edinburgh High Risk Study [13,[32][33][34][35], further six were conducted in the USA [36,37,[40][41][42][43] and further two in Asia [38,45]. We are presenting them according to the studied cognitive domain and possibly similar affected brain regions ( Table 4).…”
Section: Functional Neuroimaging Studies Of Individuals At Genetic Himentioning
confidence: 99%
See 1 more Smart Citation
“…Hemispheric laterality in relatives of schizophrenia patients has mainly been investigated with functional imaging during language tasks. Sommer et al (2004), Whyte et al (2006), and Li et al (2007) reported significantly de-creased lateralization of activity in the inferior frontal gyrus, caused by higher right (Sommer et al, 2004;Whyte et al, 2006) or lower left (Li et al, 2007) frontal activation. Structural imaging has so far focused on medial temporal asymmetry (Keshavan et al, 2002).…”
Section: Introductionmentioning
confidence: 92%
“…In addition, asymmetry has been proposed as the basis of speech and other behavioural traits (Sherman et al 1982;Rogers & Andrew 2002;Hutsler & Galuske 2003;Toga & Thompson 2003) and abnormal asymmetry appears to associate with several neuropathologies including schizophrenia (Li et al 2007), autism (Escalante-Mead et al 2003) and neuronal degenerative diseases (Toth et al 2004). In the last decade, experimental studies have provided valuable insights into the developmental basis of brain asymmetry.…”
Section: Introductionmentioning
confidence: 99%